Patients Who Benefit from Intracranial Pressure Monitoring without Cerebrospinal Fluid Drainage After Severe Traumatic Brain Injury. Issue 2 (25th July 2018) - Lele, Abhijit; Kannan, Nithya; Vavilala, Monica S; Sharma, Deepak; Mossa-Basha, Mahmud; Agyem, Kwesi; Mock, Charles; Pandey, R M; Dash, H H; Mahapatra, Ashok; Gupta, Deepak
Abstract: BACKGROUND: India has a high traumatic brain injury (TBI) burden and intracranial pressure monitoring (ICP) remains controversial but some patients may benefit. OBJECTIVE: To examine the association between ICP monitor placement and outcomes, and identify Indian patients with severe TBI who benefit from ICP monitoring METHODS: We conducted a secondary analysis of a prospective cohort study at a level 1 Indian trauma center. Patients over 18 yr with severe TBI (admission Glasgow coma scale score < 8) who received tracheal intubation for at-least 48 h were examined. Propensity-based analysis using inverse probability weighting approach was used to examine ICP monitor placement within 72 h of admission and outcomes. Outcomes were in-hospital mortality and Glasgow Outcome Scale (GOS) score at discharge, 3, 6, and 12 mo. Death, vegetative, or major impairment defined unfavorable outcome. RESULTS: The 200 patients averaged 36 [18 to 85] yr of age and average injury severity score of 31.4 [2 to 73]. ICP monitors were placed in 126 (63%) patients. Patients with ICP monitor placement experienced lower in-hospital mortality (adjusted relative risk [aRR]; 0.50 [0.29, 0.87]) than patients without ICP monitoring. However, there was no benefit at 3, 6, and 12 mo. With ICP monitor placement, absence of cerebral edema (aRR 0.54, 95% confidence interval 0.35-0.84), and absence of intraventricular hemorrhage (aRR 0.52, 95% confidence interval 0.33-0.82) were associated with reduced unfavorable outcomes. CONCLUSION: ICP monitor placement without cerebrospinal fluid drainage within 72 h of admission was associated with reduced in-patient mortality. Patients with severe TBI but without cerebral edema and without intraventricular hemorrhage may benefit from ICP monitoring.